Production of polyhydroxybutyrate and hydroxyapatite (PHB/HA) composites for use as biomaterial - Santos,G. A. dos (2017)
Abstract The composite materials using polyhydroxybutyrate as matrix and hydroxyapatite as reinforcement (PHB/HA) were produced by molding, using pressing at 100 MPa and 165 °C for 30 min. The amount of filler was varied from 0 to 20 wt% to evaluate the effect of the HA particles on mechanical properties and the bioactivity of the composites. The increase of the HA amount reduced the compressive strength of the composites nearly 20% while bending strength reduced nearly 30%. However, the bioactivity after 14 days immersion in SBF was improved with the increase of HA amount, with formation of apatite layer on the surface of the PHB/HA composite.